2018
DOI: 10.1002/ijc.31575
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, smoking, and risk of Her2‐overexpressing and triple‐negative breast cancer relative to estrogen receptor‐positive breast cancer

Abstract: Epidemiological evidence is limited on how alcohol consumption and smoking are associated with risk of different subtypes of breast cancer, such as triple-negative (TN) and human epidermal growth factor receptor 2-overexpressing (H2E) breast cancers, which may have different etiologies from more common luminal (estrogen receptor [ER+]) breast cancers. In this population-based case-case study, we evaluated the association between alcohol, smoking, and risk of H2E and TN breast cancer, compared with ER+ breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The strong association between smoking and breast cancer risk for both ILC and IDC subtypes in our study is in agreement with the findings of previous studies . A meta‐analysis on 14 published cohort studies based on 73,388 women suggests that active smoking is associated with an increased risk of all subtypes of breast cancer in women who initiate smoking before the birth of their first child .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The strong association between smoking and breast cancer risk for both ILC and IDC subtypes in our study is in agreement with the findings of previous studies . A meta‐analysis on 14 published cohort studies based on 73,388 women suggests that active smoking is associated with an increased risk of all subtypes of breast cancer in women who initiate smoking before the birth of their first child .…”
Section: Discussionsupporting
confidence: 92%
“…Participants were asked about their education (primary or illiterate, intermediate, high school, academic), occupation (housewife, employed), ethnicity (Fars, Lor, Turk, other), family history of breast cancer (no, second relative, first relative/both first and second relatives), smoking during adolescence and adulthood (yes, no), history of oral contraceptive (OCP) use (ever, never), history of chest X‐ray (yes, no), history of benign breast disease (yes, no), physical activity (30 min or more of moderate aerobic exercise at least three times per week on a regular basis) (yes, no), body mass index (BMI; defined as <24.9, 25.0 to 29.9 and ≥30.0 kg/m 2 ), deliberate weight loss after 18 years of age (yes, no), age at first delivery (<18, 18–23, 24–30, ≥31 years and nulliparous), total number of months of breastfeeding for all children (0–5, 6–17, 18–29, 30–41, ≥42 months), history of miscarriage (yes, no), menarche age (<12, 12–13, ≥14 years), regular menstrual (yes, no), menopausal status (premenopausal, postmenopausal), and diagnosed with type 2 diabetes (yes, no).…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol per se can increase sex hormone levels and subsequently stimulate proliferation of estrogen-receptor positive cells [32]. The available evidence is consistent for a causal association between alcohol consumption and hormone receptor-positive tumors (otherwise luminal type) with inconclusive or no association with hormone receptor-negative tumors [33,34]. It has been suggested that the enzymatic machinery responsible for the elimination process of alcohol (alcohol dehydrogenase and aldehyde dehydrogenase) may not be sufficient during periods of binge drinking [35].…”
Section: Discussionmentioning
confidence: 99%
“…[48] The presence of three receptors (triple-positive breast cancer cells) was reported with increased sensitivity of chemotherapeutic compound toward breast cancer cells due to nonselective binding of tested chemotherapeutic compounds toward receptors hence contribute for permeant bindings of compounds toward receptors, indeed it prevented the binding of ligand and hormone, followed by activation of respective signaling cascade to order the downstream molecules to destruct the cell surface-bound receptors thus inhibited proliferation of cancer cells. [49] In present studies, the cytotoxic activity of PTZ toward proliferation of MCF-7 breast cancer cells was conducted via MTT viability assay. By treating the tested compound toward breast cancer cells for 24 hours, the PTZ showed proliferation-cytostatic effects in dose-dependent manner ( Figure 1A rounding the MCF-7 cancer cells, thus it is a useful method to check probability of PTZ in inducing secondary inflammation toward the surrounding normal cells in breast).…”
Section: Discussionmentioning
confidence: 99%